Sharing Session: Menjadi Akuntan Muda yang Berkualitas dan Berintegritas - A, Yeni Lestari; Hartono, Trifina Caroline; Malinda, Okta (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STAI Al Fithrah Surabaya, 2024)
This sharing session aims to provide knowledge and motivation to the community, especially students, to become accountants with quality and integrity at a young age. Accountants play an important role in companies, especially in analyzing financial reports. Having accountants can improve the quality of financial reports and attract public trust. The method used is a direct approach, namely presentation and discussion with the presenter. This Sharing Session discusses the profile of IAI (Institute of Indonesia Chartered Accountants), Getting to Know Accounting Services Firms, developments in accounting & technology, and strategies for becoming a young accountant. The students were very helpful in this sharing session because it not only discussed how to become a young accountant with quality and integrity but also provided students with more knowledge about the IAI (Institute of Indonesia Chartered Accountants) so that students not only become ordinary accountants but also motivated students to be more enhance accounting education.